A detailed process design for conventional friction stir welding of aluminum alloys and an overview of related knowledge. Issue 2 (24th September 2020) - El‐Moayed, Mohamed H.; Shash, Ahmed Y.; Rabou, Mahmoud Abd; El‐Sherbiny, Mahmoud G.
Abstract: Friction stir welding (FSW) has matured considerably since its introduction in 1991. Over the last decades, it has indeed branched and been applied in different fields, such as automotive, aerospace, railway, and shipbuilding. This article aims to survey the basic knowledge related to the conventional FSW of aluminum alloys in order to provide a tool for understanding the friction stir processes. The review covers the five basic process parameters: rotational speed, welding speed, tool geometry, tilt angle, and plunge depth. Furthermore, it presents the related equations and recommended ranges of those parameters to facilitate the process design step for industrial implementation. A sample of 30 published articles was drawn for that purpose. The current article also discusses the main five properties most researchers are interested in, namely, microstructure, microhardness, tensile strength, residual stresses, and distortion. Abstract : ‐ This review work discusses the friction stir welding process of aluminium alloys, highlighting the five parameters that are essential for the process to take place. ‐ It presents the data extracted from thirty published articles, using this data, the authors of the current overview managed to deduce the common operating speeds, the common tool material, the common tool features, and two empirical equations required for tool design. ‐ It gives an overview of weldment properties such as microstructure, microhardness, tensile strength, residual stresses, and distortion.